2015
DOI: 10.4049/jimmunol.1402409
|View full text |Cite
|
Sign up to set email alerts
|

CD14++CD16+ Monocytes Are Enriched by Glucocorticoid Treatment and Are Functionally Attenuated in Driving Effector T Cell Responses

Abstract: Human peripheral monocytes have been categorized into three subsets based on differential expression levels of CD14 and CD16. However, the factors that influence the distribution of monocyte subsets and the roles which each subset plays in autoimmunity are not well studied. Here we show that circulating monocytes from patients with autoimmune uveitis exhibit a skewed phenotype towards intermediate CD14++CD16+ cells, and that this is associated with glucocorticoid therapy. We further demonstrate that CD14++CD16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 47 publications
5
51
0
4
Order By: Relevance
“…Whether, this latter subset displays suppressive function is controversial. For some authors, these cells do produce the antiproliferative cytokine IL-10 or induce T reg s, [44][45][46] whereas for others, they highly express HLA-DR and release the proinflammatory cytokine tumor necrosis factor a. 47 Proliferation Index [27][28][29]39 M-MDSCs were recently defined, in tumor-bearing mice, as the most immunosuppressive subset.…”
Section: Discussionmentioning
confidence: 98%
“…Whether, this latter subset displays suppressive function is controversial. For some authors, these cells do produce the antiproliferative cytokine IL-10 or induce T reg s, [44][45][46] whereas for others, they highly express HLA-DR and release the proinflammatory cytokine tumor necrosis factor a. 47 Proliferation Index [27][28][29]39 M-MDSCs were recently defined, in tumor-bearing mice, as the most immunosuppressive subset.…”
Section: Discussionmentioning
confidence: 98%
“…TNF α signaling has been extensively implicated as a driver of systemic loss of vascular resistance and shock during EVD. Glucocorticoids have been less well studied in EVD, but decrease MHC-II ex vivo (Hawrylowicz et al, 1994) and in vivo during sepsis (Tulzo et al, 2004) and reduce CD14 expression (Nockher and Scherberich, 1997) while increasing the abundance of DP monocytes (Liu et al, 2015) . Indeed, the connection between EVD and sepsis may be direct: studies have found bacterial invasion during EVD in NHPs (Reisler et al, 2018) and in humans (Carroll et al, 2017) , with immune signatures that resemble sepsis (Eisfeld et al, 2017) .…”
Section: Discussionmentioning
confidence: 99%
“…Данные о влиянии глюкокортикоидов на субпопуляци-онный состав моноцитов у больных РА отсут-ствуют. Тем не менее показано, что при ауто-иммунном увеите терапия глюкокортикоидами приводит к селективному накоплению промежу-точных (CD14++CD16+) моноцитов, которые ин-гибируют пролиферацию Т-клеток и индуцируют генерацию Т-рег [38]. Относительно биологиче-ских препаратов L. Chara c соавт.…”
Section: Discussionunclassified